STRATEGY AND SUSTAINABILITY ANALYSIS OF DRAGON FRUIT AGRIBUSINESS MANAGEMENT (HYLOCEREUS SPP.) (Cases at Sabila Farm and Buah Naga Geulis Garden) - Br Tarigan, Artanininai
Dragon fruit agribusiness (Hylocereus spp.) requires good management so that its sustainability is guaranteed. Some dragon fruit plantations on the island of Java stopped operating due to problems in agribusiness management that could not be handled properly. This study aims to analyze sustainable dragon fruit agribusiness management. Cultivation analysis includes aspects of nursery, planting, maintenance, and postharvest. Business feasibility analysis and sustainability analysis include ecological, social and institutional, and financial aspects. The study was conducted at Sabila Farm (SF) Yogyakarta and Naga Geulis Fruit Garden (KBNG) Subang. SF Net Present Value (NPV) value is IDR 650.575.643, while KBNG NPV value is IDR 18.446.788.359. The SF Break Even Point (BEP) was Rp. 89.385.261 (2,979.18 kg), while the KBNG BEP value was Rp. 638,636,883 (21,287.90 kg). Internal Rate of Return (IRR) in SF and KBNG are 40,7% and 50,6% respectively (with a discount rate of 10%). Influence of inflation in the analysis of economies of scale is positive, and sensitivity analysis shows production capacity as a factor of production with the highest sensitivity to total production costs. Based on these results, it can be stated that the dragon fruit business is feasible and profitable. The sustainability of dragon fruit cultivation management in SF has an index of 58.95% and KBNG worth 62.25% so that it can be stated that the two plantations have been managed sustainably. The implementation of dragon fruit cultivation in both plantations was in accordance with good agriculture practices (GAP) in dragon fruit cultivation. Recommendations on sustainable agribusiness management strategies of dragon fruit cultivation in order to become the center for good quality dragon fruit production, include the application of efficient lighting, re-planting the unproductive plant, development of target markets, development of processed products, development of maintenance Standard Operating Procedures (SOPs), human resource development, and collaboration with universities for research and innovation. and with relevant associations or business entities to support the development of product distribution networks.